Pengaruh Ukuran Perusahaan, Leverage, dan Profitabilitas terhadap Nilai Perusahaan - Andrian, Maichel; Dwiyanto, Bambang Sugeng (Universitas Proklamasi 45, 2025)
This study examines the influence of firm size, leverage, and profitability on firm value. Firm size is measured using the Natural Logarithm (ln) of Total Assets, leverage with the Debt to Equity Ratio (DER), profitability with Return on Equity (ROE), and firm value with Price to Book Value (PBV). This is a quantitative study with a sample of 55 consumer goods industry companies listed on the Indonesia Stock Exchange (IDX) (275 data points), selected through purposive sampling. Data was obtained from the IDX website and relevant companies. The study was analyzed using descriptive statistics, basic and classical assumption tests, multiple linear regression, as well as F and t-tests with the assistance of SPSS 20. Based on the F-test results, the three variables collectively have a significant influence on firm value. Meanwhile, the t-test results indicate that firm size has a significantly negative effect, leverage has a significantly positive impact, and profitability has a significantly negative influence on firm value.